Splenic morphometric characteristics in infectious mononucleosis (ultrasonic study) - S. A. Perepelitsa (Sankt-Peterburg : NIIÈM imeni Pastera, 2021)
The spleen is a secondary immune and the largest organ of the reticuloendothelial system, actively involved during infectious mononucleosis. Clinically, assessing a degree of organ involvement in the pathological process seems unlikely. As a rule, only palpation and percussion are used to determine the size of the spleen, which represents a late and subjective sign of potential splenomegaly. Ultrasound examination provides ample opportunities to estimate the spleen size during infectious mononucleosis. Our study was aimed at identifying morphometric and Doppler ultrasound changes in the spleen in patients with infectious mononucleosis. Materials and methods. There were enrolled 24 patients with infectious mononucleosis to be compared with 30 healthy medical institute students in control group. All participants underwent splenic ultrasound examination. Spleen echotexture and contour clarity together with measuring linear dimensions: length, width, and thickness were analyzed. Splenic artery and vein velocity parameters were measured at the gates of the spleen. Elastographic window for fibroelastometry was positioned within the window for standard grayscale examination. Measurements were performed at 5 or more points of the spleen parenchyma at least 4—5 mm away from the capsular zone and the zone of large vessels. Based on the morphometric measurements obtained, the mass, spleen mass coefficient (SMC), as well as the spleen mass/body height ratio and spleen mass/body surface area ratio were calculated. Results. We found that patients with infectious mononucleosis had the length, thickness and weight of the spleen significantly greater than those observed in control group. However, the mass of the spleen varies widely and justified to calculate the CMS as an objective criterion to assess the size of the spleen. It was revealed that infectious mononucleosis may proceed in one of the three variants of the splenic response: decreased size, CMR < 1.5; normal size, CMR ranged from 1.5 to 4; splenomegaly, CMR > 4. Splenomegaly is associated with increased organ stiffness, peak blood flow velocity and pressure in v. lienalis, as well as periportal lymphadenopathy. Identified changes are characteristics of young patients. Conclusion. Ultrasound examination of the spleen is of high diagnostic value for patients with infectious mononucleosis allowing highly accurate assessment state of the immune organs in the acute disease period. At the preclinical stage, gradation of splenomegaly is possible depending on its intensity, assessed hemodynamics and organ stiffness.